The values of freedom and the moral foundations of freedom-centred justice - Intropi, P (2019)
What role should freedom play in a theory of justice? In this thesis I defend the view that freedom has non-specific value (i.e. that there is value in having freedom as such and not only in having certain specific valuable freedoms), and I examine the moral foundations of freedomcentred justice (i.e. of a theory of justice that is concerned with distributing freedom as such). The main contribution of this thesis consists in offering an in-depth examination of two distinct classes of reasons that justify attributing non-specific value to freedom: axiological reasons that appeal to the good, and deontic reasons that appeal to the right. Good-based accounts include the views that interpret the value of freedom in person-affecting terms – especially, the Benefit View, which attributes personal value to freedom – as well as views that claim that it is impersonally good that persons have freedom. I focus then on examining the different senses in which people benefit from having freedom (Benefit View), since freedom is objectively valuable for the achievement of wellbeing, agency, autonomy, and human excellence. I also put forward a critique of the perfectionist foundations of freedomcentred justice, and I examine whether the moral foundations of freedom-centred justice can appeal exclusively to the Benefit View, or whether freedom-centred justice must (also) appeal to deontic reasons. I put forward a critique of moralised accounts of the value of freedom, and I defend a nonmoralised interpretation of the Status View – i.e. the view that interprets the value of freedom in deontic terms and that appeals to the value of refraining from interfering with people’s freedom in recognition of people’s moral status as agents. In particular, I argue that interference with people’s freedom is pro tanto disvaluable, including when it is directed at preventing people from performing severely wrong actions, if in ideal theory we take people’s lack of disposition to act immorally as parametric (i.e. if we assume full compliance). Finally, I argue that distinguishing between the Benefit View and the Status View has implications for the conceptual analysis of freedom, shedding light on debates concerning the relations between freedom and ability: freedom is an interpretative concept and different ways of valuing freedom inform, and can actually determine, what freedom is (i.e. the definition of freedom).